‘It’s Enough That the Goddess Knows’: About Vows and Spectacular Offerings in Popular South Indian Hinduism - Marianne Pasty-Abdul Wahid (Religions)
Votive offerings are one of the most common devotional practices in Hindu temples of Kerala and are today resorted to by an ever-growing number of worshippers seeking divine help in times of need. As this article will show, these offerings are deeply embedded in the logics of the hyper-personalized and unmediated devotion that characterizes popular Hinduism in this part of India. They are also markers of the recent opening of religion to individual contribution and intervention, as well as active tools for the intimate worshipper–deity relationship. Ritual arts conducted as votive offerings allow us to dive even deeper into these considerations and open up new alleys of analysis, for they connect public and private worlds in specific ways and introduce unique aesthetic and transactional dimensions. This article draws on extensive ethnographic fieldwork conducted in the south Indian state of Kerala, with particular focus on the ritual performing art muṭiyēṯṯu’, which is mainly conducted as a votive offering in high-caste temples devoted to the goddess Bhadrakāḷi. It pulls together anthropology, performance, and religious studies to analyze the current grassroot-level realities of lived popular religion through the prism of votive offerings in general and of ritual performing arts conducted as votive offerings in particular.